(untitled) (Philological Studies, 2019)
The main analytical aim in this article is to address some contemporary tendencies of national and religion identity in Bosnia and Herzegovina. On the ground basis of some sociology references (mainly works by Anthony Smith, Benedict Anderson and Adrian Hastings) the question of national identity has important investigatory attention. Importance of the religion identity in Bosnia and Herzegovina with its four, and since lately, three religion communities can be linked to the similar importance of the developing practices of national identity. By putting those two practices inside one phenomenon, this article operates with formulations such as «nationalization of religion» and «religionization of nation». That analytic approach opens new set of some important issues that are crucial for understanding identity policies in contemporary Bosnia and Herzegovina.